Umbra Dei. A Theological Interpretation of Psychological Life - Pędrak, Anna (Teologia w Polsce, 2020)
The article is a result of research on the phenomenon of life. Due to the multiplicity of definitions, it should be understood on many planes. The author reflects in particular on one of the levels of perceiving life as psyche, which together with bios and zoe permeate each other and interact with each other. Therefore, the subject matter of work, apart from the theological interpretation, is supported by the results of research in other scientific disciplines. Inspired by the theological category of St. Bonaventure, the author allegorically calls psychological life (intelligent and conscious) the umbra Dei – a shadow of God. This approach allows us to answer questions about the relationship between the life of psyche and the Creator and draws attention to the transcendental function visible already at this level. The Primordial Light is the Creator and the Cause of Life. With his grace He penetrates the mind and heart of man, directs him from the very beginning of creation towards God, renews his wounded nature and provides answers to existential questions that always accompany the life of a rational being – the human person.